ADAPTASI KUESIONER RESPECT & RESPONSIBILITY SCHOOL CULTURE SURVEY UNTUK SETING PENDIDIKAN - Wangi, Eneng Nurlaili; Rosiana, Dewi; Aslamawati, Yuli (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2023)
There are two main moral values that represent other moral values in forming character in educational settings, namely respect and responsibility. Even though in practice teachers have made efforts to teach character education in schools, currently in Indonesia there are still minimal instruments that can describe the effectiveness of instilling attitudes of respect and responsibility carried out by students, teachers, school staff and parents. This research aims to adapt the Respect & Responsibility School Culture Survey instrument, compiled by Davidson, Lickona, & Khmelkov (2004). This instrument measures the perceptions of students, teachers, school staff and parents regarding school culture regarding the extent to which other people in the school environment show mutually respectful and responsible behavior. Respondents in this study were elementary school students in grades 5 and 6 (N = 1096), parents and teachers and staff (N = 295) who lived in Bandung City. The test results show this instrument is reliable. The validity test also showed that the instrument for adult respondents had 15 valid items and the instrument for child respondents had 21 valid items. This instrument can be used to describe the implementation of character education in elementary schools in Indonesia